2006
DOI: 10.1016/j.neuron.2006.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Arc/Arg3.1 Is Essential for the Consolidation of Synaptic Plasticity and Memories

Abstract: Arc/Arg3.1 is robustly induced by plasticity-producing stimulation and specifically targeted to stimulated synaptic areas. To investigate the role of Arc/Arg3.1 in synaptic plasticity and learning and memory, we generated Arc/Arg3.1 knockout mice. These animals fail to form long-lasting memories for implicit and explicit learning tasks, despite intact short-term memory. Moreover, they exhibit a biphasic alteration of hippocampal long-term potentiation in the dentate gyrus and area CA1 with an enhanced early an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
683
4
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 755 publications
(726 citation statements)
references
References 43 publications
(41 reference statements)
37
683
4
2
Order By: Relevance
“…A recent study in this Journal (Gallitano-Mendel, Izumi et al 2007) found that when the transcriptional IEG Egr3 is knocked out, mice show a hyperactive response in the open field. These authors suggest that the absence of this IEG, which transcribes the effector IEG Arc (Li, Carter et al 2005) and regulates long term potentiation (LTP) and long term depression (LTD) of neuronal synapses (Plath, Ohana et al 2006), results in open field hyperactivity due to decreased habituation to its novelty. Consistent with this, impaired expression of the IEG Arc is associated with deficient long term memory and increased exploration of a novel object (Plath, Ohana et al 2006).…”
Section: Link Between Between Behavioral and Ieg Changes During Isolamentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in this Journal (Gallitano-Mendel, Izumi et al 2007) found that when the transcriptional IEG Egr3 is knocked out, mice show a hyperactive response in the open field. These authors suggest that the absence of this IEG, which transcribes the effector IEG Arc (Li, Carter et al 2005) and regulates long term potentiation (LTP) and long term depression (LTD) of neuronal synapses (Plath, Ohana et al 2006), results in open field hyperactivity due to decreased habituation to its novelty. Consistent with this, impaired expression of the IEG Arc is associated with deficient long term memory and increased exploration of a novel object (Plath, Ohana et al 2006).…”
Section: Link Between Between Behavioral and Ieg Changes During Isolamentioning
confidence: 99%
“…These authors suggest that the absence of this IEG, which transcribes the effector IEG Arc (Li, Carter et al 2005) and regulates long term potentiation (LTP) and long term depression (LTD) of neuronal synapses (Plath, Ohana et al 2006), results in open field hyperactivity due to decreased habituation to its novelty. Consistent with this, impaired expression of the IEG Arc is associated with deficient long term memory and increased exploration of a novel object (Plath, Ohana et al 2006). LTD (which is associated with altered IEG expression) is also associated with impaired spatial memory (Nakao, Ikegaya et al 2002) and brief exposure to stressful situations (Xu, Anwyl et al 1997).…”
Section: Link Between Between Behavioral and Ieg Changes During Isolamentioning
confidence: 99%
“…IEGs, like the transcription factors, c-fos and zif/268, and the effector, activity-regulated cytoskeleton-associated gene (arc), contribute to the promotion and maintenance of synaptic plasticity (Rial Verde et al 2006), associative learning Malkani et al 2004), and long-term storage and retrieval of memories (Guzowski et al 2000;Hall et al 2001;Thomas et al 2002;Bozon et al 2003;Plath et al 2006). The expression of all of these IEGs is transiently induced by cocaine (Graybiel et al 1990;Young et al 1991;Moratalla et al 1992;Bhat and Baraban 1993;McGinty 1994, 1995;Fosnaugh et al 1995;Tan et al 2000;Fumagalli et al 2006) and cocaineassociated cues (Brown et al 1992;Crawford et al 1995;Everitt and Robbins 2000;Neisewander et al 2000;Ciccocioppo et al 2001;Thomas et al 2003: Zavala et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Okuno et al (12) reported that Arc plays a role in the inverse synaptic tagging of silent synapses; Arc accumulated in silent synapses to reduce surface AMPA receptors (12). Thus, Arc is a unique molecule involved in the control of synaptic plasticity (10,13,14). Kawashima et al (4) demonstrated that a distal enhancer, synaptic activity-responsive element (SARE), which contains binding sites for cAMP-response element (CRE)-binding protein (CREB), myocyte enhancer factor 2 (MEF2), and serum response factor (SRF), located Ϫ7 kbp upstream of the Arc transcription start site, was essential for activity-dependent transcriptional activation of Arc (4).…”
mentioning
confidence: 99%